Estudo e concepção de motor de passo impulsionado por ímãs auxiliares - Yokoyama, Diogo Hitoshi (2021)
Stepper motors are devices widely used in several industries, these motors are commonly used in measurement and control applications, such as inkjet printers or even more complex systems such as aerospace systems. One of the reasons that make these motors so versatile is their way of driving, in which pulses are converted into discrete angular displacements allowing a load to be positioned in open-loop operation. In this work, a new stepper motor topology is proposed, in which permanent magnets are positioned both on the rotor and on the stator in order to increase the overall torque, with emphasis on static characteristics. The operation of this motor is done through the manipulation (reinforcement/weakening) of the magnetic field generated by the magnets of the stator using coils. In order to validate this system, the simplest arrangement was used, which has three poles in the stator and two in the rotor, facilitating the construction process and reducing the computational cost. Simulations were done using software Ansys Maxwell, in which it was possible to study the dynamics of the system and analyze the influence of some constructive parameters on the motor behavior.